Paediatric rheumatology: a subspecialty in its infancy that is making leaps and bounds - Ooi, Pei Ling (Singapore Med J, 2014)
Paediatric rheumatology is an exciting field exploding with new knowledge of autoimmune and autoinflammatory conditions and how to treat them. It is, however, a relatively new subspecialisation in Asia. There is thus a great need to educate the public and medical community about paediatric rheumatic diseases so that children with such conditions are given the highest possibility of achieving normal function in their daily lives.